Islamic theology between tradition and challenge of modernity - Grabus, Nedžad (Islam and Christian-Muslim relations, 2012)
A number of different approaches to the interpretation of cognition have always existed side by side within Islam, from those relying mainly on the basic sources - the Qur'an and the Sunna - to those that attempt to clarify the issue of cognition largely by way of rational and logical argumentation, as is the case with philosophical texts. For this reason it is important to consider the literature that emerged in the classical period, which is still being brought to light and which this article endeavours to make more accessible to present-day readers. The debate that took place between the main theological schools of the Muʿtazilīs, Māturīdīs and Ashʿarīs is of great significance for present-day readers, since it provides an insight into the emergence and development of the substantive contents of systematic belief in Islam. From the late eleventh to the early twentieth century, Muʿtazilism was seen as anathema in most of the Muslim world, and only the Māturīdīs and the Ashʿarīs were accepted among Sunnis. At the end of the nineteenth century, a critical traditionalist movement appeared, led by Muḥammad ʿAbduh (d. 1905) and Sayyid Aḥmad Khān (d. 1898). Many scholars have associated the interest in Muʿtazilī learning in the early twentieth century with the renaissance (nahḍa) in Arabic literature in the late nineteenth century. The nahḍa emerged in response to the challenges of Western civilization's irresistible cultural penetration into the Arab world, which was frozen in conservatism. Muḥammad ʿAbduh, aware of the changes that had occurred in the Muslim world as a result of Western colonialism, was trying to respond to the challenges with which social and political change confronted Muslims, and in the ideas he articulated he revived some Muʿtazilī theses.